Cost estimation : methods and tools - Mislick, Gregory K.; Nussbaum, Daniel A., 1943- (Hoboken, New Jersey : Wiley, 2015)
"Provides a step-by-step introduction to the need for cost estimation, the various applications, and the available resources for obtaining relevant data"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Costs, Industrial -- Estimates; Production management; BUSINESS & ECONOMICS -- Management Science; TECHNOLOGY & ENGINEERING -- Operations Research; BUSINESS & ECONOMICS -- Production & Operations Management; Costs, Industrial -- Estimates; Production management; Electronic books